A new livebearing fish, Heterandria tuxtlaensis, from Lake Catemaco, Veracruz, Mexico (Cyprinodontiformes: Poeciliidae) - Mceachran, John D.; Dewitt, Thomas J. (Zootaxa, 2008)
A new species of poeciliid fish, Heterandria tuxtlaensis sp. n., is described from Lake Catemaco in southern Veracruz, Mexico. Based on traditional and geometric morphometrics, H. tuxtlaensis differs most substantially from its likely sister species H. bimaculata in possessing short dorsal and caudal fins, a short dorsal fin base composed of fewer fin rays, a more shallow body, and a relatively small basicaudal spot restricted to the area above the mid lateral line. Description of this new species brings the number of known endemics in Lake Catemaco to six. This high level of endemicity complements genetic and geological findings suggesting the lake is ancient and well separated from surrounding fish populations.